Simulation of virtual time norms for technological processes - Tamošaitis, Romualdas; Gargasaite, Leonarda (Journal of Business Economics and Management, 2003)
The methodology presented in the article is based on the simulation of technological process duration, restricting on the available information about total duration of complex technological process in the conditions when there are no possibilities to determine the time norm by traditional methods. This methodology allows determining the time norm of repetitive technological processes with a defined probability without additional measurement of time for every technological process. When more information about the duration of complex technological process duration is gathered, the methodology lets to make the additional correction of separate process time norm, also increasing the reliability of the revised time norm. The methodology lets to reduce the number of technological process duration measurements, promptly evaluate the objective changes of the time norm, occurred because of the new technologies, new equipment and skills of workers.First Published Online: 14 Oct 2010